Compensatory mechanisms for methylglyoxal detoxification in experimental & clinical diabetes - Schumacher, Dagmar; Morgenstern, Jakob; Oguchi, Yoko; Volk, Nadine; Kopf, Stefan; Gröner, Jan; Nawroth, Peter Paul; Fleming, Thomas; Freichel, Marc (Molecular metabolism, 2018)
Objectives - The deficit of Glyoxalase I (Glo1) and the subsequent increase in methylglyoxal (MG) has been reported to be one the five mechanisms by which hyperglycemia causes diabetic late complications. Aldo-keto reductases (AKR) have been shown to metabolize MG; however, the relative contribution of this superfamily to the detoxification of MG in vivo, particularly within the diabetic state, remains unknown. - Methods - CRISPR/Cas9-mediated genome editing was used to generate a Glo1 knock-out (Glo1−/−) mouse line. Streptozotocin was then applied to investigate metabolic changes under hyperglycemic conditions. - Results - Glo1−/− mice were viable and showed no elevated MG or MG-H1 levels under hyperglycemic conditions. It was subsequently found that the enzymatic efficiency of various oxidoreductases in the liver and kidney towards MG were increased in the Glo1−/− mice. The functional relevance of this was supported by the altered distribution of alternative detoxification products. Furthermore, it was shown that MG-dependent AKR activity is a potentially clinical relevant pathway in human patients suffering from diabetes. - Conclusions - These data suggest that in the absence of GLO1, AKR can effectively compensate to prevent the accumulation of MG. The combination of metabolic, enzymatic, and genetic factors, therefore, may provide a better means of identifying patients who are at risk for the development of late complications caused by elevated levels of MG.